Evaluating soil moisture estimation from ground‐penetrating radar hyperbola fitting with respect to a systematic time‐domain reflectometry data collection in a boreal podzolic agricultural field. Issue 6 (3rd January 2020) - Illawathure, Chameera; Parkin, Gary; Lambot, Sébastien; Galagedara, Lakshman
Abstract: The upper 30 cm of the soil profile, which hosts the majority of the root biomass, can be considered as the shallow agricultural root zone of most temperate crops. The electromagnetic wave velocity in the soil obtained from reflection hyperbolas in ground‐penetrating radar (GPR) data can be used to estimate soil moisture (SM). Finding shallow hyperbolas in a radargram and minimizing the subjective error associated with the hyperbola fitting are the main challenges in this approach. Nevertheless, we were motivated by the recent improvements of hyperbola fitting algorithms, which can reduce the subjective error and processing time. To overcome the difficulty of finding very shallow hyperbolas, we applied the hyperbola fitting method to reflections ranging from 27‐ to 50‐cm depth using a 500‐MHz centre‐frequency GPR and compared the estimated moisture with vertically installed, 30‐cm‐long time‐domain reflectometry (TDR) sensors. We also compared TDR and GPR sample areas in a 2‐D plane using different GPR survey types and different hyperbola depths. SM measured with TDR and GPR were not significantly different according to Mann–Whitney's test. Our analyses showed that a root mean square error of 0.03 m 3 m −3 was found between the two methods. In conclusion, the proposed method might be suitable to estimate SM with an acceptable accuracy within the root zone if the soil profile is fairly uniform within the application depth range. Abstract : GPR hyperbola fitting method was applied to reflections ranging from 27‐ to 50‐cm depth using a 500‐MHz center‐frequency GPR and compared the estimated soil moisture with vertically installed, 30‐cm‐long TDR probes. A systematic TDR data collection was performed to be compatible with the GPR sampling volume. We compared TDR and GPR sample areas in a 2‐D plane using different GPR survey types and different hyperbola depths.